Evaluation of Various Free Software Options for Catphan 504 Phantom Analysis - Lorena Cunha Fernandes; Maira Ribeiro dos Santos; Leonardo Peres da Silva; Thiago Viana Miranda Lima; Rafael Figueiredo Pohlmann Simões (Brazilian Journal of Radiation Sciences)
In computed tomography, image quality tests are important to guarantee a correct medical diagnosis and a better cost and benefit for the patient. Purpose: the purpose of this study is to analyse the images reconstructed with different thorax and bone convolution filters using popular free-use software in the field of medical physics, for the Catphan 504 phantom. Methods: a total of 14 scans were performed using the chest protocol, with convolution filters (FC) FC30, FC35, FC50, FC51, FC52, FC53, FC55, FC56, FC80, FC81, FC83, FC84, FC85, FC86, on the 16-channel Canon Aquilion Lightning CT scanner using the Catphan 504 phantom. Image quality parameters evaluated were: noise, uniformity, linearity of CT numbers, and high spatial resolution with MTF 50% and MTF 10%. The images were evaluated using software such as ImageJ, Script Python, and free software for automatic evaluation of the Catphan 504 phantom, CTQA-cp, SPICE-CT, and Pylinac. Results: the tests carried out with the Catphan 504 phantom were analysed by the software and agreed with each other (with p>0.05), except for Pylinac. The results obtained with Pylinac had a significant difference for the uniformity, slice thickness, and MTF10% tests, this being the code that was the furthest away from the results obtained by the other codes. Conclusions: the ImageJ, Spice-CT, and CTQA-cp software showed consistent results for the tests performed, while Pylinac had limitations in calculating the standard deviation for the noise test and showed significant differences in some tests when compared to the other software.